On Multipliers of Hilbert Algebras (European Journal of Pure and Applied Mathematics, 2024)
This paper explores the concept of multipliers in Hilbert algebras, unveiling various intriguing properties. We delve into the intricate relationships between fixed sets, kernels, and near filters of multipliers, shedding light on their interconnected roles within Hilbert algebras. This investigation aims to provide a deeper understanding of algebraic structures and their dynamic interactions.
Keywords: Hilbert algebra; multiplier; kernel; fixed set; near filter